COVID-19: Clinical and epidemiological aspects in the interior of the Brazilian Amazon (Research, Society and Development, 2022)
COVID-19 is a pathology caused by the SARS-CoV-2 virus, which can negatively affect infected individuals, ranging from mild to moderate or severe symptoms. The first case of COVID-19 was reported in Brazil on February 26, 2020. As the WHO and world health authorities work to contain the outbreak, the health crisis has significant repercussions on human health and the well-being of the population. This is a quantitative, observational, descriptive and cross-sectional epidemiological study whose data were made available through the State Monitoring System of the epidemiological surveillance sector of the Pará State Health Department. It aims to carry out an epidemiological and clinical analysis of confirmed cases of COVID-19 in the municipality of Santarém-PA. It was identified that, from January to December 2021, there were 15,539 confirmed cases and the epidemiological profile was of female patients (55.67%), aged between 30-39 years (21.89%) and with 3.65% (567) of the cases progressed to death, the majority being men. Regarding the clinical profile, the most frequent symptoms were cough (63.84%), fever (761.1%), headache (49.78%) and sore throat (48.83%). While the most reported morbidities were, respectively, diabetes (3.26%), heart disease (1.99%) and immunodeficiency/immunodepression (0.88%). It can be concluded that these data corroborate epidemiological analyzes in the state of Pará, contributing at the informational level to new actions in the health field.